A survey on Chinese Language training needs from law student, National Institute of Justice in Luang Prabang, Lao PDR as preparedness for Operating Lao-China express train - VANNAPHA, Phetpaseuth; PHANNALATH, Sengaloun; LASY, Anousith; LATTANASOUVANNAPHONH, Champa (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This study focuses on two objectives: 1). study the current situation of teaching-learning Chinese language in urban Luang Prabang and 2). survey on the Chinese language training needs of law students at National Institute of Justice in Luang Prabang (NIJL) as preparedness for operating Lao-China express train. The preparedness is Secondary data and interview are used for objective (1), 200 questionnaires are used for objective (2). The research found that as preparedness for operating the Lao-China express train, the current situation of teaching-learning of Chinese language training is increasingly offered by both public and private language centers. The Chinese courses are designed for short and long term training, especially there is only Souphanouvong University offers bachelor degree in Chinese Language and other language schools are offered 1-6 month-Course and 9 Month-Course. Since the impact of COVID-19, some private schools offer Chinese as a foreign language as well as some students taking Chinese courses online. The study also shows that the quality of Chinese training services in Luang Prabang still requires high proficiency and efficiency from teaching staff and facilities. In summary, the survey on Chinese language training needs for the readiness of operating express trains by law students at NIJL found that the main respondents are interested in learning Chinese and it is essential for the law profession.